A Comparison of Oral Sensory Effects of Three TRPA1 Agonists in Young Adult Smokers and Non-smokers - Hansen, Eva Ø.; Arendt-Nielsen, Lars; Boudreau, Shellie A. (Frontiers in Physiology, 2017)
This study profiled intra-oral somatosensory and vasomotor responses to three different transient receptor potential (TRP) channels, subfamily A, member 1 (TRPA1) agonists (menthol, nicotine, and cinnamaldehyde) in smoking and non-smoking young adults. Healthy non-smokers (N = 30) and otherwise healthy smokers (N = 25) participated in a randomized, double-blinded, cross-over study consisting of three experimental sessions in which they received menthol (30 mg), nicotine (4 mg), or cinnamaldehyde (25 mg) chewing gum. Throughout a standardized 10 min chewing regime, burning, cooling, and irritation intensities, and location were recorded. In addition, blood pressure, heart rate and intra-oral temperature were assessed before, during, and after chewing. Basal intra-oral temperature was lower in smokers (35.2°C ± 1.58) as compared to non-smokers (35.9°C ± 1.61) [F(1, 52) = 8.5, P = 0.005, post hoc, p = 0.005]. However, the increase in temperature, heart rate, and blood pressure in response to chewing menthol, nicotine, and cinnamaldehyde gums were similar between smokers and non-smokers. Although smoking status did not influence the intensity of burning, cooling, and irritation, smokers did report nicotine burn more often (92%) than non-smokers (63%) [χ(1, N=55)2 = 6.208, P = 0.013]. Reports of nicotine burn consistently occurred at the back of the throat and cinnamaldehyde burn on the tongue. The cooling sensation of menthol was more widely distributed in the mouth of non-smokers as compared to smokers. Smoking alters thermoregulation, somatosensory, and possibly TRPA1 receptor responsiveness and suggests that accumulated exposure of nicotine by way of cigarette smoke alters oral sensory and vasomotor sensitivity.